Electromyographic analysis of trunk muscles during the golf swing performed with two different clubs - Marta, S.; Silva, L.; Vaz, J.; Bruno, P.; Pezarat-Correia, P. (International Journal of Sports Science and Coaching, 2013)
The aim of this study was to compare the EMG patterns of trunk muscles throughout the golf swing, performed with two different clubs, and also to describe the activity patterns in the average golfer. Nine male golfers performed ten swings using the pitching wedge and the 4-iron, alternately. Surface electromyography (EMG) was recorded from trunk muscles of both sides: rectus abdominis (RA), external oblique (EO), erector spinae (ES) and gluteus maximus (GM). 3D high-speed video analysis was used for determination of golf swing phases. Muscles had their highest activation during the forward swing and acceleration phases. The highest mean activation regarding the maximal EMG (EMGMAX), was found in the right EO (59-67% EMGMAX) and in the GM of the trailing leg (62- 72% EMGMAX). In the majority of the cases and phases, trunk muscles showed higher mean values of EMG activation when golfers performed with 4-iron club. However, no club effect was verified in trunk muscles.